An Anti-Transhumanist Reading of Stef Smith’s Girl in the Machine - Yalçın Erden (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
It is an undeniable fact that transition periods are painful processes that are difficult for society to embrace, regardless of the novelty or convenience they offer. Indeed, such circumstances arouse doubt and anxiety among the affected people due to their unpredictable nature. As a result, society has adopted a mostly hesitant attitude toward the process, with such hesitation being reflected in the literary works of the current age, in which exponential technological progress is experienced and human agency is questioned. Although the utopian optimism of transhumanist philosophy cannot be ignored, the rising number of dystopian works in all walks of contemporary literature signifies humanity’s current anxiety about rapid technological changes and digital transformation. Stef Smith, a promising Scottish playwright, also questions automation technology, addiction to mobile devices, human microchipping, uploading, and the impact of artificial intelligence on humans through her play Girl in the Machine (2017). The playwright focuses on the daily interactions between Owen and Polly, a passionate couple. In the play, she demonstrates a world order in which not only human values are distorted but also the lives of the characters are devastated after a specific device with artificial intelligence, Black Box, becomes a part of their family. In this way, she reveals her doubts about the transhumanist anticipation of human enhancement through technology. Accordingly, this paper aims to interrogate the anxiety about unrestrained technological developments and transhumanist ideals by analysing Smith’s play from an anti-transhumanist perspective. Most importantly, it attempts to highlight that the play, as a dystopian work, functions to caution humanity against an impending existentialist crisis in the shade of digitalisation.